Increasing Students' Physics Learning Outcomes through Experiential Learning Model - Nurnaifah, Ihfa Indira; Anggriani, Sri; Zulpiah, Ayu; Wahyuni, Sri (Universitas Muhammadiyah Makassar, 2023)
This research is a classroom action research which involves planning, action, observation, reflection, and re-planning. This study aims to find out: 1) the application of the experiential learning model to physics learning at MAN Pinrang; and 2) the improvement of students’ physics learning outcomes at MAN Pinrang through the application of the Experiential Learning Model. The location of this study is MAN Pinrang, Paleteang District, Pinrang Regency. The subjects of the study were students of class X MIPA MAN Pinrang consisting of 40 people. This research was conducted through 2 cycles. The results show that the in the first cycle, 72.5% of the students’ scores exceeded the Minimum Completion Criteria (KKM) score with the highest score of 90 and the average score of 74.1. This result indicates that the students’ physics learning outcomes improved compared to the test results on the pretest. Furthermore, the students' physics learning outcomes increased again in cycle II, with the highest score of 98 and the average score of 84.05 while the minimum completion percentage was 95%. Having the success in fulfilling the learning indicators and the completion value of 80%, it can be concluded that the experiential learning model was effective for improving the students’ Physics Learning outcomes at MAN Pinrang. Hence, this experiential learning model should be applied to improve student physics learning outcomes in the future.